There and back again: development and regeneration of the zebrafish lateral line system. (20th October 2014) - Thomas, Eric D.; Cruz, Ivan A.; Hailey, Dale W.; Raible, David W.
Abstract: The zebrafish lateral line is a sensory system used to detect changes in water flow. It is comprised of clusters of mechanosensory hair cells called neuromasts. The lateral line is initially established by a migratory group of cells, called a primordium, that deposits neuromasts at stereotyped locations along the surface of the fish. Wnt, FGF, and Notch signaling are all important regulators of various aspects of lateral line development, from primordium migration to hair cell specification. As zebrafish age, the organization of the lateral line becomes more complex in order to accommodate the fish's increased size. This expansion is regulated by many of the same factors involved in the initial development. Furthermore, unlike mammalian hair cells, lateral line hair cells have the capacity to regenerate after damage. New hair cells arise from the proliferation and differentiation of surrounding support cells, and the molecular and cellular pathways regulating this are beginning to be elucidated. All in all, the zebrafish lateral line has proven to be an excellent model in which to study a diverse array of processes, including collective cell migration, cell polarity, cell fate, and regeneration. WIREs Dev Biol 2015, 4:1–16. doi: 10.1002/wdev.160 This article is categorized under: Nervous System Development > Vertebrates: Regional Development Adult Stem Cells, Tissue Renewal, and Regeneration > Regeneration